The Prevalence and Determinants of Active Tuberculosis among Diabetes Patients in Tertiary Care Hospitals of Nepal 2018 - Kharel, R. K.; Sultana, R.; Bichaa, R. P.; Pant, R. P.; Weerakoon, A. P.; Karki, K. B. (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2019)
Introduction: Researches implicated diabetes as independent risk factor for multi-drug resistant tuberculosis and unfavorable outcome of treatment. There is no data to address the association between diabetes mellitus (DM) and tuberculosis (TB) in Nepal. Thus we assessed the burden and demographics of active tuberculosis among diabetic patients attending tertiary care hospitals in Nepal. Methods: A cross-sectional study was conducted in adult DM patients attending seven tertiary care hospitals representing five development region of the country. Relevant data were collected and participants were screened for active TB (symptom screening and microbiological diagnosis). Results: Among the 520 enrolled DM patients screened, 23 had active TB. The prevalence was 4.42% (CI 2.96 - 6.54). The positive cases had older age group with the mean age of 59.73 ± 17.36 years with male predominance of 78% (18/23). Among the 23 positive cases, only two (8.69 %) had extra pulmonary TB. Diabetic control had significant (p=0.006) relationship to develop Tuberculosis. The comorbid conditions e.g., Hypertension (OR 13, 95% CI: 4.54 to 37.14); diabetic nephritis (OR 9.25, 95% CI: 2.03 to 42.20); and Diabetic neuropathy (OR 26.66, 95% CI: 5.16 to 137.71) are significant risk factors to develop tuberculosis among the diabetes patients. There were no significant differences in occupation, literacy rate, tobacco or alcohol consumption, HbA1c levels between TB and non-TB participants. Conclusion: The prevalence of tuberculosis among diabetic patients is low in Nepal. This is the result of tertiary care hospital outdoor patients only, thus representativeness was compromised. Thus to assess the magnitude of comorbidities, mandatory screening in all level were recommended.